The effect of a sand surface on physical performance responses of junior male handball players to plyometric training - Hammami, M.; Bragazzi, N. L.; Hermassi, S.; Gaamouri, N.; Aouadi, R.; Shephard, R. J.; Chelly, M. S. (BMC Sports Science, Medicine and Rehabilitation, 2020)
Background The effects of 7 weeks plyometric training on a stable surface and on sand were compared in junior male handball players.